1994
DOI: 10.1111/j.1525-1470.1994.tb00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate‐ and Delayed‐Type Contact Hypersensitivity in Children Older than 5 Years With Atopic Dermatitis: A Pilot Study Comparing Different Tests

Abstract: We conducted a prospective open study of immediate- and delayed-type contact hypersensitivity to food and other allergens in 33 children with atopic dermatitis (AD). The design of the study was exploratory and not randomized. Various methods for detecting immediate-type hypersensitivity were compared. Thirty-three children age 5 to 15 years with persistent AD were initially enrolled, but 3 dropped out. Nine patients had positive reactions to foods in the patch-scratch test, four had positive reactions in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Seventeen children (43%) showed a positive reaction to nickel sulphate, similar to that reported in earlier studies [1, 7, 11, 14, 15]. In a previous study in Rotterdam, the most positive patch test reactions in children aged 5–15 years were to nickel, cobalt and balsam of Peru [8]. However, in the study by Kohl et al [16], metals (predominantly nickel) were listed only in third place, behind cosmetics and topical drugs as the cause of ACD in children.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Seventeen children (43%) showed a positive reaction to nickel sulphate, similar to that reported in earlier studies [1, 7, 11, 14, 15]. In a previous study in Rotterdam, the most positive patch test reactions in children aged 5–15 years were to nickel, cobalt and balsam of Peru [8]. However, in the study by Kohl et al [16], metals (predominantly nickel) were listed only in third place, behind cosmetics and topical drugs as the cause of ACD in children.…”
Section: Discussionsupporting
confidence: 75%
“…ACD was suspected in all patch-tested children. In an earlier prospective open study in 33 children with atopic dermatitis (aged 5–15 years), Oranje et al[ 8] reported 14 of 33 children with positive patch test reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Cobalt chloride and potassium dichromate were also frequent sensitizers, as were fragrance markers (fragrance mix I, fragrance mix II, Myroxylon pereirae and hydroxyisohexyl‐3‐cyclohexenecarboxaldehyde) . When children with and without AD referred for patch testing were compared, the risks of sensitization to fragrance mix I and Myroxylon pereirae were significantly associated with AD (4·1% vs. 2·6%, P < 0·01; and 3·5% vs. 2·5%, P < 0·02, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Sensitizations to foods can be investigated by means of in vivo tests (skin prick tests, prick‐prick tests) and in vitro tests (serum specific IgE). A positive test will reflect sensitization, but may have poor correlation with clinical allergic responses . In addition, atopy patch tests proved to be useful for studying delayed food‐related skin responses …”
Section: Avoidance Strategies On the Basis Of Allergy Diagnosismentioning
confidence: 99%